Paid work after retirement: Recent trends in Denmark - Mona Larsen; Peder J. Pedersen (Institute for the Study of Labor (IZA), 2012)
The labor market in Denmark seems to follow the trend in a number of other countries of increasing labor force participation in the 60+ group. We analyze trends for the early retirement age interval 60-64 and for the age group 65-74 where people are eligible to a national social security program from age 65. Until now, the increase in labor force participation has been most pronounced among 60-64-year-olds and among women. We find significant impact on work after retirement from education, gender, home ownership, aggregate unemployment at the time of retirement, age and education. Being married has a positive impact for men and a negative impact for women. We relate labor force participation after retirement to the cyclical situation and to the several policy reforms introduced since 1980.
urn:nbn:de:101:1-201208174818
Keywords: H55; J14; J26; 330; labor force participation; retirement; Rentner; Erwerbstätigkeit; Alte Menschen; Dänemark